Examining consumer responses to YouTube ads through facial expressions and self-reports: the role of gender identity and emotional appeals - Voutsa, Maria C.; Tsichla, Eirini; Hatzithomas, Leonidas; Margariti, Kostoula (My University, 2021)
The study focuses on the value of gender identity as a moderator in the relationship between consumers' experienced and self-reported joy towards a YouTube video advertisement. In a laboratory experiment, participants were exposed to an emotional advertising appeal (aggressive versus warm) and their self-reports were compared with their facial expression analysis. The results show that in the warm advertising scenario, high masculine individuals who experienced joy tends to mask their emotions and under-report their level of joy. A similar reaction was recorded for low masculine individuals exposed to the aggressive advertising scenario. Self-reported joy acts, also, as a mediator of the impact of experienced joy on consumers' attitudes and purchase intentions. The findings raise significant concerns regarding the appropriateness of relying solely on self-report measures when examining constructs susceptible to social desirability issues, yielding important implications for both academics and practitioners.
Keywords: Gender identity; Emotional appeals; Advertising; Facial expression analysis